2015
DOI: 10.15282/ijame.11.2015.42.0223
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Shaft Speed Control Using a Magnetorheological Brake

Abstract: This paper presents a performance evaluation of a shaft speed control using a magnetorheological brake (MR brake). The MR brake consists of a rotating disk that is immersed in magnetorheological fluid (MR fluid). The rheology of the fluid changes under the influence of a magnetic field. Two controllers are proposed in this work: onoff and proportional-integral-derivative (PID). The on-off controller acts as the benchmark controller through computer simulation and experimental testing. Load tests have been cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Patil and Sawant [16] investigated reliability issues in case of MR brake for automotive application. Some control studies on MR brake have been reported by Abdulla et al [17]. All these works have focused on shear mode MR brake, and the order of torque output reported in various works is far too less in view of high torque demanding application like automotive application.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Patil and Sawant [16] investigated reliability issues in case of MR brake for automotive application. Some control studies on MR brake have been reported by Abdulla et al [17]. All these works have focused on shear mode MR brake, and the order of torque output reported in various works is far too less in view of high torque demanding application like automotive application.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…In [20], a conventional PID controller was designed for a tension control, and the experiment results showed the feasibility and better control effect for tension control of a winch spooler system. In [21], the on-off and PID controller were proposed to evaluate the controller's effectiveness in braking the wheel shaft at 50, 100 and 150N in varying speeds of 300, 500, 700 and 900 rpm; the simulation and experiment results showed that the PID controller had good performance compared with the on-off control.…”
Section: Pid Control Methodsmentioning
confidence: 99%
“…Patil [27] published the thermal analysis for an MR brake functioning in a car. Patil et al [28] examined the dependability factor of an MR braking system, while Abdullah [29] introduced an MR brake employing a PID controller at different speeds and loads.…”
Section: Introductionmentioning
confidence: 99%